Do patients with different psychiatric disorders show altered social decision-making? A systematic review of ultimatum game experiments in clinical populations. Issue 3 (4th May 2018) - Hinterbuchinger, Barbara; Kaltenboeck, Alexander; Baumgartner, Josef Severin; Mossaheb, Nilufar; Friedrich, Fabian
ABSTRACT: Background: Impairments in social functioning are a common feature of psychiatric disorders. Game paradigms pose a unique way for studying how people make decisions in interpersonal contexts. In the last decade, researchers have started to use these paradigms to study social decision-making in patients with psychiatric disorders. Purpose: The aim of this systematic literature review is to summarise the currently available evidence on the behaviour of patients with psychiatric disorders in the commonly used Ultimatum Game (UG). Method: A systematic literature search including MEDLINE, PsycINFO, PSYNDEXplus Tests, PSYNDEXPLUS Literature, EBM Reviews—Cochrane Central Register of Controlled Trials, Embase and PASCAL was performed via the Ovid interface. Results: We found evidence for alterations in UG behaviour for patients with frontotemporal dementia, schizophrenia, affective disorders, alcohol, cocaine, heroin and 3, 4-methylenedioxymethamphetamine consumption, alcohol dependence, anxiety disorders, borderline personality disorder, autism, Tourette syndrome and oppositional defiant disorder. Conclusion: There is some evidence that different psychiatric disorders might go along with alterations in social decision-making. However, in general, data are currently limited and studies are hard to compare due to differences in methodologies.